Escritórios de projetos na área de tecnologia de informação: um modelo discriminante do contexto para a sua criação - Spelta, Andrea Giovanni (2009)
Projects Management Offices (PMOs) are organizational entities charged with various responsibilities concerned with the management of the organization’s projects. Because of accelerated investment in information technology (IT) and the increased strategic importance of those investments, creation of such entities became more intense in the 1990s outside the context of project-oriented firms. Although some large companies did create PMOs in their IT areas (IT-PMO), others chose not to, which suggests the following research question: what are the organizational conditions that justify and do not justify the creation of IT-PMO? The research design used to address this question consisted in developing and testing a conceptual model of the drivers of the decision to create an IT-PMO. The model was inductively developed from incentives to create or not create PMOs as reported in the literature and found in four case studies with large privately-owned, non-project oriented Brazilian companies. This model was then tested empirically through the application of discriminant analysis to data collected from 40 large Brazilian companies. It was found that only two among the four drivers present in the initial model are statiscally significant, namely the satisfaction with IT project portfolio control and the management’s favorable opinion on PMOs. The reduced model, represented by the the discriminant function, resulted statiscally significant, with a very satisfactory rate of correct classifications of new observations. This study contributes to the development of project management theory by improving the understanding of the context that makes companies take the decision to create or not to create an IT-PMO. To practioners, the rule derived from the discriminant function may be a very helpful element for executives considering whether or not to create an IT-PMO at their companies, assisting them in making more effective decisions.